An assay for entry of secreted fungal effectors into plant cells. Issue 2 (26th September 2016) - Lo Presti, Libera; Zechmann, Bernd; Kumlehn, Jochen; Liang, Liang; Lanver, Daniel; Tanaka, Shigeyuki; Bock, Ralph; Kahmann, Regine
Summary: Successful colonization of plants by prokaryotic and eukaryotic pathogens requires active effector‐mediated suppression of defense responses and host tissue reprogramming. Secreted effector proteins can either display their activity in the apoplast or translocate into host cells and function therein. Although characterized in bacteria, the molecular mechanisms of effector delivery by fungal phytopathogens remain elusive. Here we report the establishment of an assay that is based on biotinylation of effectors in the host cytoplasm as hallmark of uptake. The assay exploits the ability of the bacterial biotin ligase BirA to biotinylate any protein that carries a short peptide (Avitag). It is based on the stable expression of BirA in the cytoplasm of maize plants and on engineering of Ustilago maydis strains to secrete Avitagged effectors. We demonstrate translocation of a number of effectors in the U .  maydis– maize system and show data that suggest that the uptake mechanism could be rather nonspecific The assay promises to be a powerful tool for the classification of effectors as well as for the functional study of effector uptake mechanism not only in the chosen system but more generally for systems where biotrophic interactions are established.